PENGEMBANGAN SELF CONFIDENCE PADA SISWA SD (Jurnal Pendidikan Dasar, 2019)
This article aims to identify or assess the confidence of elementary school studentsbased on the results of a review of the Bandura theory and the results of recent research. Thescope of study of these problems includes the concept of self confidence, the factors formedand processes that affect the development. The benefits based on the kajisan content of thisarticle are expected to be able to support in developing a self confidence learning strategy.Based on the findings of the observation, there is still a loss of confidence in students, especiallywhen faced with challenges or new situations when the learning process takes place. Thiscertainly results in a low sense of self-confidence through various smart efforts that can developa sense of self-confidence in students more developed through various strategies andapproaches to better learning. The results developed in the learning strategy are able to fosterconfidence. The method used in this discussion uses the review literature review method basedon the results of the latest research.